2020
DOI: 10.1299/jfst.2020jfst0008
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study toward optimization of blowing and suction locations for improving lift-to-drag ratio on a Clark-Y airfoil

Abstract: Reynolds-averaged Navier-Stokes simulations (RANS) of flows around a Clark-Y airfoil with uniform blowing (UB) and uniform suction (US) are performed aiming at improvement of the airfoil performance. First, the control effect in the case with single UB or US applied on the airfoil surface is investigated at the various control locations. The magnitude of UB/US is 0.14% of the free-stream velocity, and the control region is set at four different locations on the upper and lower surfaces. The Reynolds number bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…The discussion of the difference and meaning of the body and wake-survey drag in presence of fluid sources, object of the present manuscript, may seem trivial at first to an expert aerodynamicist and has been discussed, albeit not directly in the context of flow control, in classic literature such as by Schlichting & Gersten (2006) [43, pag.311]. Nonetheless, recent works on the topic of turbulent drag reduction via wall-normal blowing [24,29,30], including ours [22,25], overlooked this aspect or did not address it properly, thereby possibly overestimating the control performance by not considering the inclusive drag or pointing at an only apparent disagreement of the different drag measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discussion of the difference and meaning of the body and wake-survey drag in presence of fluid sources, object of the present manuscript, may seem trivial at first to an expert aerodynamicist and has been discussed, albeit not directly in the context of flow control, in classic literature such as by Schlichting & Gersten (2006) [43, pag.311]. Nonetheless, recent works on the topic of turbulent drag reduction via wall-normal blowing [24,29,30], including ours [22,25], overlooked this aspect or did not address it properly, thereby possibly overestimating the control performance by not considering the inclusive drag or pointing at an only apparent disagreement of the different drag measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In apparent contradiction to this expectation numerical studies of airfoils with blowing reveal a significant reduction of the total drag experienced by the airfoil [22,24]. Furthermore, it was shown that the scheme of uniform blowing on the pressure side of an airfoil has a prospect of significant performance enhancement resulting from both pressure and friction drag reduction [25].…”
Section: Introductionmentioning
confidence: 98%
“…Wing dari UAV menggunakan airfoil jenis Clark Y, dengan alasan airfoil tersebut memiliki bentuk geometri yang sederhana dan banyak diaplikasikan pada pesawat kebanyakan UAV fixed wing, selain itu jenis airfoil tersebut mampu meminimalkan drag ketika sedang terbang (Ohashi et al, 2020), serta airfoil jenis ini dapat memberikan coefficient lift yang lebih tinggi dari jenis lainnya sehingga dapat cepat menghasilkan gaya angkat pada sudut serang minimum (Dhafin at al., 2019).…”
Section: Metode Penelitianunclassified
“…Sedangkan untuk jenis airfoil yang dipilih yang akan digunakan pada sayap UAV dipilih airfoil Clark-Y dengan alasan selain bentuk geometri airfoil tersebut yang lebih sederhana dan cocok bagi pemula, terlebih airfoil tersebut juga dapat meminimalisir drag friction pada saat terbang [18]. Selain daripada itu alasan lainnya pemilihan airfoil Clark-Y untuk komponen dari sayap UAV yang akan didesain adalah karena airfoil jenis ini memiliki nilai coefficient lift yang lebih tinggi dari jenis lainnya sehingga dapat cepat menghasilkan gaya angkat [19].…”
Section: Pemilihan Airfoilunclassified